Educating in freedom (Journal of Parents and Teachers, 2026)
The article addresses a question posed by parents regarding how they might raise their children in a spirit of freedom. Rather than offering recipes or instructions, the author suggests certain attitudes and behaviours exhibited by those who bring up their children in a spirit of freedom. A free person naturally accepts differing opinions, respects the freedom of others, knows how to listen, does not presume to be right, and is able to relate to others with ease. On the other hand, for the author, freedom can coexist well with laws, regulations and rules; indeed, laws must be for the sake of human freedom.
Keywords: educating in freedom; respect; trust; listening; different viewpoints